THE EFFECTS OF PROTECTIONIST POLICIES ON INTERNATIONAL TRADE - Demir, Merve; Sepli, Ayçe (PEOPLE: International Journal of Social Sciences, 2017)
Globalisation, which is the most important feature of the new economic world order, reflects the elimination of all barriers to trade of goods and services among countries. Liberalisation of the international trade is the sine qua non condition of the new economic order. As the sources are limited and needs are limitless, no country can meet their needs with their own sources. Therefore, international economic relations are emerged as the most significant element of global foreign trade. Liberalisation movement has especially accelerated after the Second World War. Governments cannot implement any protectionist policy in terms of their interests as the practices that started with the General Agreement on Tariffs and Trade (GATT) and then continued with the World Trade Organisation (WTO) have restricted protectionist measures. Although free trade is robust in theory as a requirement of globalisation, in practice it is hard to see international trade of goods and services without any restriction. Thanks to international treaties, tariffs were reduced, however, invisible barriers to trade have emerged. Governments have usually applied protectionist policies, particularly following the global financial crises, though they engaged with the principles of globalisation. As long as protectionist policies have been implemented, neoliberal paradigm has temporarily shifted. Moreover, developing countries have difficulties as protectionist measures bring several standards in practice. It is therefore argued in this study that protectionist measures create a paradox in terms of free trade.